2012
DOI: 10.1063/1.3674164
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the [MgO3]+ cation

Abstract: Accurate ab initio calculations are performed to investigate the stable isomers of [MgO(3)](+) and its lowest electronic states at both molecular and asymptotic regions. The calculations are done using large basis sets and configuration interaction methods including the complete active space self-consistent field, the internally contracted multi-reference configuration interaction, the standard coupled cluster (RCCSD(T)) approaches and the newly implemented explicitly correlated coupled cluster method (RCCSD(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In 2008, Yazidi et al 14 investigated the corresponding reaction pathways. For reaction (2), Rowe et al 9 evaluated the rate constant to be 1 Â 10 À10 cm 3 s À1 at T = 300 K. Very recently, Ben Houria et al 15 showed that ionmolecule reactions between Mg and O 3 + may lead also to the formation of Mg + but in less extent because of the lower abundance of ozone in the atmosphere compared to O 2 and O. For reaction (4), the measured rate constant is 2.3 Â 10 À10 cm 3 s À1 (at T = 300 K).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Yazidi et al 14 investigated the corresponding reaction pathways. For reaction (2), Rowe et al 9 evaluated the rate constant to be 1 Â 10 À10 cm 3 s À1 at T = 300 K. Very recently, Ben Houria et al 15 showed that ionmolecule reactions between Mg and O 3 + may lead also to the formation of Mg + but in less extent because of the lower abundance of ozone in the atmosphere compared to O 2 and O. For reaction (4), the measured rate constant is 2.3 Â 10 À10 cm 3 s À1 (at T = 300 K).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] These species are involved in a multitude of neutral-neutral and ion-molecule reactions. Recent investigations 4,5 showed the formation of the MgO 3 and MgO 3 + tetratomic superoxides through the reactions of atomic Mg, MgO or MgO 2 molecules with O, O 2 or O 3 appropriate neutral or ionic partners. Specifically, Ben Houria et al 5 pointed out the crucial role of the OMgOO + complex cation during the reactive collisions between MgO/MgO + and O 2 + /O 2 ;…”
Section: Introductionmentioning
confidence: 99%
“…5 of ref. 5 shows the corresponding reaction path: the reactive collisions between Mg + + O 3 lead to the formation of the OMgOO + ( 2 A 0 , 2 A 00 ) ion that decomposes later to form MgO + + O 2 . Such reactions should influence the local and global concentrations of the neutral and ionic Mg, O 3 , O 2 species in the Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations